Promoting Toko Aneka Gelas Through a Promotional Video - Ronaldo Joshua (Kata Kita: Journal of Language, Literature, and Teaching, 2021)
Toko Aneka Gelas was established in 1998. It is located at Saranani No.39, Makassar. Toko Aneka Gelas is the shop that sells household in category of tableware like glass, plate, jar, etc. The average the products sold in the shop is made of glass. Toko Aneka Gelas has a problem that must be solved immediately which is Toko Aneka Gelas experienced decrease sales since five years ago. Therefore, the best solution to solve this problem is to make a promotional video. The reason why a promotional video is the best solution to overcome the problem is because it can help increase the customer and also can attract the new target customer which is Café owners. The promotional video was made following Colman (2019) in order to make good promotional video. The solution will give three benefits according to Mishra (2015). The benefits are: it is increasing brand awareness, segment identification, and the customer traffic. Keywords: promotional video, sales, promoting